Seasonal variation in diet and prey availability in the wall lizard Podarcis vaucheri (Boulenger, 1905) from the Djurdjura Mountains, northern Algeria. Issue 1 (9th August 2019) - Mamou, Rabah; Marniche, Faïza; Amroun, Mansour; Exbrayat, Jean-Marie; Herrel, Anthony
ABSTRACT: We studied the composition and seasonal changes in diet and prey selection in the wall lizard Podarcis vaucheri of the Djurdjura Mountains throughout its activity period, from April to October 2014. The analysis of 238 faecal pellets revealed 1 206 prey items distributed in 19 prey categories. The most important prey categories were: Formicidae, Coleoptera, Aranea, Homoptera, and Orthoptera. Significant seasonal variation in the taxonomic composition of the diet and prey availability was found. A significant difference in diet composition was observed between males and females in spring. This lizard species displayed a more diverse dietary spectrum during this period, followed by a slight decrease in summer. However, a severe decrease in the food niche breadth was observed in autumn, resulting in a high consumption of ants. A comparison of diet composition and prey availability showed that lizards exhibited a clear selection of certain prey types, in contrast to what is often suggested for lacertid lizards.